UPAYA GURU PEMBIMBING MENGATASI KESULITAN BELAJAR MELALUI BIMBINGAN BELAJAR DI SMA NEGERI 1 KOTA BENGKULU - Evi Valendri (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2017)
This study aims to: (1) Determine the form of learning difficulty students in SMA Negeri 1 Kota Bengkulu, (2) Determine the supervising teacher attempts to overcome the difficulties of learning through tutoring in SMA Negeri 1 City of Bengkulu. The method used is method kualitatif- informants in this study were all school personnel with observation, documentation, and interviews withtechnique. snowball sampling Data analysis techniques used in the study of reduction and editing, data presentation, interesting kesimpulandan verification. Having done the research findings of the study revealed that: The shape of difficulty for students at SMA Negeri 1 City of Bengkulu in general there are two kinds of internally (from inside) and ektern (from the outside). Form of learning difficulty in the lack of student interest due to laziness, boredom, and saturated in learning. Because feeling lazy and not interested in learning the students become spirit and they are out of the classroom or chatting with friends. Additional learning activity makes students trouble dividing their time and dereliction of duty. Efforts to overcome the difficulties of learning tutor students through tutoring during this time to the classical with time is also limited and not maximized. Then to groups or individuals still called. No keasadaran students to come alone, as in SMA 1 still exist views on students who entered the room BK is troubled students is thus difficult students come voluntarily and realize their need for counseling. Cooperation tutor with school personnel, such as teachers and homeroom subjects is still lacking and is not maximized. During this cooperation existed only indirectly. Students who were called were sometimes given guidance has not been up that only limited guidance only. Keywords: Teacher Advisor, Learning Disabilities and Tutoring